Pengenalan Aplikasi Desain Grafis Figma pada Siswa-Siswi Multimedia SMK PGRI 2 Sidoarjo - Ayouvi Wardhanie; Kristin Lebdaningrum (Yumary: Jurnal Pengabdian kepada Masyarakat, 2023)
Purpose: This workshop would be led by the students, enhancing their new capability to operate the Figma application to prepare for their future careers in graphic design. Methodology: The method applied to this workshop was divided into three stages, such as preparation, implementation, and report. in the first stage, we identified problems and asked permission from partners regarding the schedule of the workshop and then module creation. In the second stage, we conducted training on the use of the Figma application and consulted, and finally the report stage, we asked for feedback from participants and made publications. Results: Most of the students felt very enthusiastic about learning the Figma application, this can be seen from the questionnaire where out of a total of 23 people, 9 people gave a score of 5 which means they were very satisfied with the workshop held, 9 people gave a score of 4 which means satisfied, 3 people gave a value of 3 which means quite satisfied, and the remaining 2 people stated that they were not satisfied with the material presented Conclusions: Students have gained new knowledge related to the current trend of design applications. Furthermore, they are also very enthusiastic about participating in workshop and being able to apply the material presented.